Modeling pedestrian gap acceptance behavior at a six-lane urban road. Issue 8 (30th July 2021) - Shaaban, Khaled; Muley, Deepti; Mohammed, Abdulla
Abstract: The illegal crossing behavior of pedestrians at unmarked mid-block sections is unsafe, risky, and increase the potential of severe conflicts and crashes, especially in the case of multilane roads. This paper investigates the pedestrians' gap acceptance while crossing the road illegally at an unmarked mid-block segment of a six-lane divided urban road. A multiple regression model was developed to estimate the size of the accepted gaps as a function of the demographics, crossing behavior, and traffic-related characteristics. The model suggested that waiting time, crossing point, rolling gap, vehicle speed, critical distance, and vehicle position have a strong influence on the size of the gap. The findings of this study can be useful for simulation modeling, enforcement efforts, and education and training programs.